139 Comparison of histological and diffusion-weighted MRI techniques in the analysis of post mortem multiple sclerosis brains. Issue 3 (9th February 2012) - Kolasinski, J; Stagg, C J; Chance, S; Esiri, M; Chang, E; Palace, J A; McNab, J A; Jenkinson, M; Miller, K; Johansen-Berg, H
Abstract : Multiple sclerosis (MS) is a chronic inflammatory neurological condition characterised by both focal and diffuse neurodegeneration and demyelination throughout the central nervous system. However, associations between these individual pathological processes remain poorly defined. Here we present a highly novel combination of whole brain post-mortem diffusion and structural MRI with quantitative histology to assess patterns of MS pathology. Two white matter tracts and their associated grey matter structures were assessed in nine fixed whole brains on the basis of their documented involvement in MS: that running from lateral geniculate nucleus to primary visual cortex, and from mediodorsal nucleus of the thalamus to prefrontal cortex. Cortical thickness was correlated significantly with both tract myelination and thalamic nucleus cell density within the anatomically distinct tract structures. Such correlations were not observed between these markers of neurodegeneration across the two tract types. In addition, diffusion MRI metrics in all tracts were correlated significantly with histologically defined levels of tract myelination. These data demonstrate for the first time the potential relevance of functional anatomical connectivity to the spread of MS pathology in a "tract-specific" pattern. Furthermore, the persisting relationship between metrics from post-mortem diffusion-weighted MRI and tissue microstructure in fixed samples validates the exciting potential of this imaging modality for future neuropathological studies.